2008
DOI: 10.1007/s10593-008-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclization of caprolactam hydrazidine by the action of 2,3-dioxopyrrolo[2,1-a]isoquinolines

Abstract: Keywords: 2-hydrazino-3,4,5,6-tetrahydro-2H-azepine, 2,3-dioxopyrrolo[2,1-a]isoquinolines, 3,3-dimethyl-1-(1,2,4-triazolo[4,5-a]azepan-8-ylcarbonylmethylideno)-1,2,3,4-tetrahydroisoquinolines, opening of the dioxopyrroline ring.In previous work [1, 2], we showed that the reaction of 2,3-dioxopyrrolo[2,1-a]isoquinolines with several dinucleophiles might proceed with opening of the lactam bond and concurrent heterocyclization. The reactions of these compounds with cyclic hydrazidines have not yet been reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…On interacting ester 2a with other hydrazides, such as cyanoacetylhydrazide and benzoic acid hydrazide in boiling glacial acetic acid or 2-propanol, no new products were isolated, which may be explained by the weak nucleophilic properties of the reactants used. It is known that 2,3-dioxopyrrolo[2,1-a]isoquinolines frequently play the role of acylating reagents, interacting with N-nucleophiles with opening of the pyrrole ring [4][5][6][7]. It therefore seemed of interest to study the acylation reaction of hydrazides with these reagents with the aim of obtaining substances analogous to compounds 5a,b in structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On interacting ester 2a with other hydrazides, such as cyanoacetylhydrazide and benzoic acid hydrazide in boiling glacial acetic acid or 2-propanol, no new products were isolated, which may be explained by the weak nucleophilic properties of the reactants used. It is known that 2,3-dioxopyrrolo[2,1-a]isoquinolines frequently play the role of acylating reagents, interacting with N-nucleophiles with opening of the pyrrole ring [4][5][6][7]. It therefore seemed of interest to study the acylation reaction of hydrazides with these reagents with the aim of obtaining substances analogous to compounds 5a,b in structure.…”
mentioning
confidence: 99%
“…The mass spectrum of compound 3 contains a peak* for the molecular ion of 300 [M] + (27), and also a peak for the 3,3-dimethyl-1-methylidenecarbonyl-1,2,3,4-tetrahydroisoquinoline fragment at 200 (35), characteristic for compounds having this fragment in their structure [4][5][6][7]. In the mass spectrum of tricyclic ketone 4a a peak was observed for the molecular ion at 284 [M] + (12), and also a peak corresponding to cleavage of the semicarbazide fragment 211 [M] + (17).…”
mentioning
confidence: 99%
“…The use of o-aminothiophenol as the binucleophile in the reaction with dioxopyrrolines 1a-d leads to benzothiazole derivatives 2c-f. We have recently shown that dioxopyrroline ring opening occurs in the reaction of pyrroloisoquinoline 1a with caprolactam hydrazidine to give the bicyclic 1,2,4-triazolo[4,5-a]azepine system [6].…”
mentioning
confidence: 99%